2022
DOI: 10.1088/1361-6455/ac8327
|View full text |Cite
|
Sign up to set email alerts
|

Ranging with a frequency-shifted feedback laser using frequency-comb driven phase modulation of injected radiation

Abstract: Theoretical and experimental data is presented for the application of an injection-seeded frequency-shifted feedback (FSF) laser for high accuracy ranging. Previous work discussed such a ranging scheme with a phase-modulated single-frequency laser where the phase modulation is done by an electro-optical modulator driven by a single frequency $\Omega$ which is swept over a certain bandwidth depending on the given experimental situation. In the present theoretical and experimental work, the phase modulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that despite certain features of FSF lasers operation, they are able to generate pico- and femto-second pulses with characteristics suitable for various practical applications: high-resolution distance ranging [ 31 , 41 43 ], atomic cooling and slowing [ 44 ], efficient optical pumping of atoms [ 45 ], dispersion measurement [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that despite certain features of FSF lasers operation, they are able to generate pico- and femto-second pulses with characteristics suitable for various practical applications: high-resolution distance ranging [ 31 , 41 43 ], atomic cooling and slowing [ 44 ], efficient optical pumping of atoms [ 45 ], dispersion measurement [ 46 ].…”
Section: Introductionmentioning
confidence: 99%